Definitive radiotherapy versus postoperative radiotherapy of patients with oro- and hypopharyngeal cancer: Impact of Prognostic Factors - Rudat, Volker; Ahmet-Osman, Salia; Schramm, Oliver (Journal of oncology, 2012)
Purpose: To compare the impact of prognostic factors of patients treated with definitive radio(chemo)therapy versus patients treated with surgery and postoperative radiotherapy for squamous cell carcinoma of the oro- and hypopharynx. Patients and Methods. 162 patients treated with definitive radiotherapy and 126 patients treated with postoperative radiotherapy were retrospectively analysed. The impact of the prognostic factors gender, age, total tumor volume (TTV), pre-radiotherapy hemoglobin level (Hb-level), tumor site, T- and N-classification, radiotherapy interruptions >5 days, radiotherapy versus simultaneous radiochemotherapy, R-status and time interval between surgery and radiotherapy were investigated. Results: The median follow-up time for the censored patients treated with definitive radio(chemo)therapy was 28.5 months and for postoperative radiotherapy 36.5 months. On univariate analysis, the TTV, Hb-level, and simultaneous radiochemotherapy had a significant impact on the survival of patients treated with definitive radio(chemo)therapy. For patients treated with postoperative radiotherapy, only the TTV showed a statistical trend for the survival (𝑃=0.13). On multivariate analysis, the TTV and simultaneous radiochemotherapy maintained their statistical significance for patients treated with definitive raditherapy, and the TTV, the statistical trend for patients treated with postoperative radiotherapy (𝑃=0.19). Conclusions: The TTV was the predominant prognostic factor for both, patients treated with definitive or postoperative radiotherapy.
Gesehen am 02.05.2018